Re-envisioning a “skills framework” to meet 21st century demands: What do young people need? - Buasuwan, Prompilai; Suebnusorn, Wanwisa; Butkatunyoo, Oraphan; Manowaluilou, Nongluck; Kaewchinda, Marid; Lalitpasan, Usanee; Srilapo, Nart; Sarnswang, Sudarat; Suksiri, Weeraphat; Wiboonuppatham, Rangsun; Sripongpankul, Saipan (Frontiers in Education, 2022)
Young people today face rapidly changing landscapes in all aspects of life. These changes pose challenges to the wellbeing of future generations and the success of the global commitment to Sustainable Development Goals (SDGs). The skills framework project was introduced to reexamine the “Life skills”/Skills Education Framework to guide the direction of twenty-first century skills in Thai Education. Skills frameworks have been developed and proposed by various organizations. In re-envisioning one for Thailand’s young people, it was crucial to involve them in the process. This paper describes a design-thinking approach to developing a skills framework involving stakeholders’ voices and, crucially, Thai children and youth. The paper argues that any skills framework for the twenty-first century must include young people’s values and aspirations. This study shows that while Thai children and adolescents share common interests and have the vision to make Thailand a prosperous nation, they differ in their focus on required skills and are also challenging some core values. The proposed basic education skills framework is designed to be comprehensive and flexible. It encompasses a global skills framework to meet twenty-first century needs and support global commitments to the SDGs. At the same, it reflects the diverse needs of Thailand’s stakeholders, especially young people. It also emphasizes the principles of applicability, adaptability and relevance and seeks to reflect the aspirations and dreams of its young people in the context of a changing environment and future demands.